Google and Alibaba’s Different Stock Performances after Antitrust Investigations, the Reasons and Enlightenment - Gu, Cong; Lv, Benfu; Peng, Geng (International Journal of Economics and Financial Issues, 2022)
Platform monopoly has attracted wide attention from politicians and the public.. The European Commission has made unremitting efforts in platform antitrust enforcement in the last decade, but together with antitrust investigations, the stock prices of platform giants like Google and Facebook keep breaking their highest points. At the end of 2020, the Chinese government also started antitrust investigations towards platform companies like Alibaba. In contrast, the stock price of Alibaba crashed and lost more than half of its market value. By analyzing their CAR, we proved that the stock performance of Alibaba is significantly worse than Google after their most serious antitrust investigations. The difference reflects investors’ different expectations of the European Commission and China’s antitrust enforcement. A noteworthy problem then comes out: while the Chinese government is seriously strengthening platform antitrust and putting forward reforms in platform regulation, is there any authority that is able to effectively regulate the international platform giants and maximize the welfare of their users worldwide?